Strategi Muslim Mempertahankan Kerukunan Umat Beragama Sebagai Wujud Nilai Pendidikan Bertoleransi di Graha Maria Annai Velangkanni Sumatera Utara Medan - Asfiati, Asfiati (IAIN Padangsidimpuan, 2020)
Religious harmony is talking about the inner atmosphere. Every religion teaches goodness and invites the truth. Muslim strategy to maintain religious harmony as a form of the value of tolerant education around Graha Maria Annai Velangkanni needs to be explored. The research method uses a sociological approach with the type of qualitative research. The subject of the research is the Muslim community who live around Graha Maria Annai Velangkanni Medan, North Sumatra. Data collection techniques through observation, in-depth interviews and discussion group forums. The results of this study indicate that the Muslim strategy to maintain religious harmony as a form of the value of tolerant education around Graha Maria Annai Velangkanni North Sumatra Medan is carried out with the following steps: Building religious harmony with the intentions and awareness of fellow humans. Build social cultures and make cooperation. Hold dialogues and meetings between religious leaders, community leaders and through social and family approaches. Creating an understanding of noble values, cultural values for dialogue in friendly and mutual respect. The motivating factors for the Muslim community to maintain religious harmony as a form of the value of tolerant education around Graha Maria Annai Velangkanni North Sumatra Medan, are: the factor of awareness and mutual raising of fellow creatures created by God. The intention factor to study different cultural and religious customs. Openness factor.